Tugas Dan Tanggung Jawab Sekretaris Dalam Menjalankan Tugasnya Pada Kantor Dinas Pekerjaan Umum Penataan Ruang Dan Perumahan Rakyat Provinsi Kalimantan Timur - Zuhriah Zuhriah; ST. Nurhasanah; Satryawati Satryawati (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2022)
Duties and Responsibilities of the Secretary in Carrying Out His Duties at the Office of the Public Works Department of Spatial Planning and Public Housing in East Kalimantan Province. This study aims to find out how the duties of a secretary in carrying out their duties in the office. In general, Business Administration is a major that studies everything about the operational activities of a company or business. The company's own operational activities include marketing, HR, secretarial, financial management, production and so on. For example, a secretary who works at the Office of Public Works, Spatial Planning and Public Housing in East Kalimantan Province, carries out the tasks assigned by the Head of the Service in accordance with his/her field of work. The Secretariat consists of the General Sub-Section, the Finance Sub- Section and the Planning Sub-Section. Each Sub Division is led by a Head of Sub Division who in carrying out his duties is under and responsible to the secretary. The author's purpose in taking the title of this Final Project is to find out how the performance process of a secretary at the Office of the DPUPR & PERA Prov. East Kalimantan. The Head of the Planning Sub-Section has the main task of leading the implementation of tasks in the Planning Section, Developing Programs, preparing materials for the preparation of technical policies in the field of transportation planning, informatics and communication as well as reports in the field of program planning.